Effects of aquatic heavy metal intoxication on the level of hematocrit and hemoglobin in fishes: A review - Ahmed, Imtiaz; Zakiya, Archo; Fazio, Francesco (Frontiers in Environmental Science, 2022)
Environmental pollution caused due to the presence of heavy metals has become a great concern as it has an adverse effect on almost all types of ecosystem. In this sense, these pollutants have a tendency to pollute the aquatic ecosystem, thus badly affecting the health of aquatic organisms. As a result, toxicological studies believe them to be the most harmful pollutants in the aquatic environment. Among all the aquatic organisms, fish—being a chief organism in this system—become the easiest victim of these pollutants. Heavy metals enter fish bodies through the alimentary system by consumption of polluted food, or through the gills, and skin. They are finally delivered by the bloodstream to the organs and tissues where they accumulate after absorption. Ultimately, in this way heavy metals make their way into humans through the food chain. The fluctuations in the hematological values may serve as an initial indicator of the toxicant’s impact on fish health. It has been observed that when pollutants impact the quality of the aquatic medium, the first consequence is apparent in the form of physiological changes in fish, which are reflected in one or more hematological parameters, such as hemoglobin, hematocrit, red blood cell count, white blood cell count, etc. As a result of these alterations, fish become weak, anemic, and more susceptible to diseases. Over the past several decades, a vast number of studies have been reported on the qualitative and quantitative variations in hematological parameters due to the presence of heavy metal intoxication. Heavy metal contamination of water resources not only degrades the water quality but also negatively impacts the quality of food in the form of fish proteins. Therefore, this article sheds light on the effects of heavy metals on hemoglobin and hematocrit of fish hematology and calls for more attention to the protection and preservation of aquatic ecosystems, particularly those contaminated with heavy metals.